Genetic Diversity and Performance: Evidence from Fooball Data - Michel Beine; Silvia Peracchi; Skerdilajda Zanaj (Center for Economic Studies and ifo Institute (CESifo), 2021)
The theoretical impact of genetic diversity is ambiguous since it leads to costs and benefits at the collective level. In this paper, we assess empirically the connection between genetic diversity and the performance of sport teams. Focusing on football (soccer), we built a novel dataset of national teams of European countries that have participated in the European and the World Championships since 1970. Determining the genetic diversity of national teams is based on the distance between the genetic scores of every players' origins in the team. Genetic endowments for each player are recovered using a matching algorithm based on family names. Performance is measured at both the unilateral and bilateral level. Identification of the causal link relies on an instrumental variable strategy that is based on past immigration at the country level about one generation before. Our findings indicate a positive causal link between genetic diversity and teams' performance. We find a substantial effect, a one-standard increase in diversity leading to ranking changes of two to three positions after each stage of a championship.
Keywords: F22; F66; O15; O47; Z22; 330; genetic diversity; football; sports team; performance; family names; migration